Discerning the margins of constitutional encroachment: The drug courier profile in the airport milieu - Williams, Christopher R. (American journal of criminal justice, 1999)
Very little is known about the legal dimensions of the drug courier profile and how it functions in relation to airport detainments. This article attempts to fill that gap by analyzing relevant case law. Further, the authors demonstrate how the United States Supreme Court struggles to balance the competing interests of the public’s need to be protected from narcotics and drug trafficking versus the citizen’s right to be protected from unlawful searches and seizures. The article closes with a brief discussion of the implications this balancing portends for the future administration of justice in this area.